eCM 2014
DOI: 10.22203/ecm.v027sa02
|View full text |Cite
|
Sign up to set email alerts
|

Cell therapy for intervertebral disc repair: advancing cell therapy from bench to clinics

Abstract: Intervertebral disc (IVD) degeneration is a major cause of pain and disability; yet therapeutic options are limited and treatment often remains unsatisfactory. In recent years, research activities have intensified in tissue engineering and regenerative medicine, and pre-clinical studies have demonstrated encourageing results. Nonetheless, the translation of new biological therapies into clinical practice faces substantial barriers. During the symposium “Where Science meets Clinics”, sponsored by the AO Foundat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 46 publications
0
51
0
Order By: Relevance
“…In pre-clinical research, one of three biological approaches is typically used to address the degenerative process: stimulating anabolic processes; modulating catabolic processes; and providing new cells 22 . Tissue-engineered cellular therapy has focused on chondrocyte 23 or stem cell replacement therapy 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In pre-clinical research, one of three biological approaches is typically used to address the degenerative process: stimulating anabolic processes; modulating catabolic processes; and providing new cells 22 . Tissue-engineered cellular therapy has focused on chondrocyte 23 or stem cell replacement therapy 24 .…”
Section: Discussionmentioning
confidence: 99%
“…During the degenerative process, the end plates thin and mineralize (58) and permeability of the end plates may decrease and hinder nutrient transport to the IVD. Strategies that serve to increase permeability of the endplates, and thus maintain nutrition to the IVD may be helpful to support the long-term survival of the endogenous or delivered cell populations (2830, 59, 60). An increased presence of nociceptive nerve fibers in the end plates of pathological motion segments is believed to be related to painful conditions with IVD disorders (61) but is very poorly understood.…”
Section: Ivd Structure Function and Pathologymentioning
confidence: 99%
“…There are a very large number of pre-clinical and now clinical studies that reported on outcomes for injection of allogeneic and autologous progenitor and stem cell populations to the IVD (see discussions in (27), (28)), and we provide a brief overview of those clinical studies that make use of biomaterials for cell or drug delivery. The outcomes for cell or drug delivery may have some overlap with the goals of engineered material approaches to restore IVD anatomy (e.g., disc height) to prevent neural impingements and associated pain, or to reverse the radiographic evidence of pathology (e.g., signal intensity upon MRI); however, the challenges to regulatory approval and high demand for cell delivery to the IVD have driven work past a mechanistic or consensus-based understanding of best practice.…”
Section: Introductionmentioning
confidence: 99%
“…2014, Benneker et al. 2014, Sakai and Andersson 2015). Patients come to see a clinician because they have back pain, not because they are worried about disc degeneration.…”
Section: Which Patients Would Benefit From Disc Repair?mentioning
confidence: 99%